Towards ecosystem-based management of shellfish aquaculture in British Columbia, Canada: an industry perspective. - Mamoser, Melanie Paula (2011)
With declining wild fisheries and increasing seafood demand from a growing population, attention has turned to aquaculture in general, and shellfish aquaculture in particular, to meet this demand. Aquaculture has grown dramatically in the last twenty years through intensification of operations and the expansion of the industry into new areas. This growth has been associated with environmental degradation and social conflict leading some to question its sustainability. However, those studying the problem point to significant opportunities for sustainable forms of aquaculture by focusing on the cultivation of species such as shellfish and the adoption of ecosystem-based management (EBM). Shellfish aquaculture has a long history in British Columbia (B.C.), Canada with an abundance of coastline and suitable water conditions. There is significant development potential for shellfish aquaculture in B.C., which creates an opportunity to ensure this development occurs in an ecologically sound way through the use of governance approaches like ecosystem-based management. Transitioning from conventional approaches to resource management to an ecosystem-based approach presents several challenges particularly for the management of one sector. This study highlights how an understanding of the industry and the existing governance context can inform the implementation of EBM. The specific research objectives include: (1) to understand the governance system for shellfish aquaculture in B.C.; (2) to understand the shellfish aquaculture industry within the context of EBM; and (3) to explore EBM as an approach to governance in the shellfish aquaculture industry in B.C. The main method of inquiry is a questionnaire survey (October 2006 to February 2008) of the shellfish aquaculture industry. Supporting methods include an analysis of industry data, an in-depth analysis of government documents, policies and regulations, and targeted interviews with federal and provincial government regulators. The empirical knowledge gained through the main research instrument was combined with the contextual knowledge gained through the supporting methods to achieve a more holistic understanding of the case study. The results show that the governance setting for the shellfish aquaculture industry is multi-lateral and the lack of comprehensive and targeted legal instruments, and the ill-use of marine spatial planning and conflicts with other coastal users have together contributed to an inefficient and costly site application process. EBM has the potential to address some of these challenges with the current governance process by making some decisions on an ecosystem-scale as opposed to an application-by-application basis, such as assessing the presence of fish habitat and consulting with stakeholders. The results of the survey of the shellfish aquaculture industry show that the industry is geographically diverse, and understands and values the connection between their business and the large ecosystem. This suggests that the industry may be supportive of EBM. However, the industry faces many economic challenges that may influence their capacity to participate, as such regulators should look towards the use of economic incentives to achieve policy objectives. Although this research provided several recommendations for management and the industry in moving forward with this new approach to governance, three fundamental elements are needed: • marine spatial planning that is integrated within the governance framework; • the integration science and management through adaptive management including an ongoing monitoring framework that informs governance strategies; and, • engaging the industry as active partners in this governance approach through co-management. This research makes significant contribution to understanding the shellfish aquaculture industry in B.C. Prior to this study there was little information available characterizing the structure and socio-economic make-up of the industry. The results of the survey and the in-depth analysis of the governance context for the shellfish aquaculture industry provide a previously unavailable base of information from which to build future studies. In addition this research contributes to the growing body of literature on EBM assessing the potential challenges and opportunities for moving the theoretical concept into practice. === Graduate